COVID 19 PADA KEHAMILAN - Islami Islami; Nor Asiyah; Nasriyah Nasriyah (Universitas Muhammadiyah Kudus, 2021)
Covid 19 is an infectious disease caused by coronavirus. This virus first appeared in Wuhan China. The manifestations of this disease vary in each person, ranging from no symptoms, mild symptoms to severe symptoms that can even cause death. Mothers who are confirmed to have Covid 19 can experience various symptoms such as those who are not pregnant. This research method is a descriptive study to describe the condition of pregnancy with the COVID 19 virus infection which is taken from various previous research sources. Result: Symptoms that appear include cough, fever and sore throat. However, in pregnant women, the placenta serves as a barrier that can prevent transmission of Covid 19 from mother to fetus. Pregnant women with comorbidities who are confirmed positive for Covid 19 increase the risk of illness and increase the need for ICU. The diagnosis of Covid 19 can be confirmed in various ways, but the gold standard that can be used as a reference for diagnosing Covid 19 is the polymerase chain reaction (PCR) culture test. The impact of pregnancy confirmed by Covid 19 is maternal mortality, preterm delivery and fetal growth disorders and fetal death.